Gender and Religiosity in Indonesian Popular Media: An Anthropological Reading of Cultural Representations - Jafar, Nuraisa; Lampe, Munsi; Muhammad, Marlisa J.; Muhammad, Darlisa; Guntur, Ahmad Ismail; Hasyim, Andi (Jurnal Lektur Keagamaan, 2025)
Digital media have become central sites for the production, circulation, and negotiation of religious meaning among young Muslims in Indonesia. While existing studies on religion and social media often rely on quantitative indicators of religiosity or focus on isolated platforms, they rarely examine how everyday digital practices function as culturally meaningful religious texts. This study addresses this gap by conceptualizing social media content as a form of popular digital religious literature within the broader Nusantara Islamic literary tradition. Drawing on qualitative digital ethnography and digital literary analysis, the study examines multimodal content produced by Indonesian Muslim youth on platforms such as Instagram, TikTok, and Twitter/X, including captions, visual Qur’anic quotations, personal narratives, and performative displays of piety. The analysis situates these digital texts within anthropological theories of lived religion, gender, and mediated authority, highlighting how religious identity is constructed through narrative, aesthetics, and platform-specific affordances. The findings show that digital platforms do not merely transmit religious messages but actively reshape religious expression by generating new genres, redefining authorship, and reconfiguring religious authority, particularly in relation to gendered piety. By framing social media practices as platformed religious literature, this study contributes to scholarship on digital religion, Islamic studies, and anthropology by demonstrating how contemporary Indonesian Islam is articulated through hybrid literary forms shaped by both tradition and algorithmic culture.